Gate‐Tunable and Multidirection‐Switchable Memristive Phenomena in a Van Der Waals Ferroelectric. Issue 29 (30th May 2019) - Xue, Fei; He, Xin; Retamal, José Ramón Durán; Han, Ali; Zhang, Junwei; Liu, Zhixiong; Huang, Jing‐Kai; Hu, Weijin; Tung, Vincent; He, Jr‐Hau; Li, Lain‐Jong; Zhang, Xixiang
Abstract: Memristive devices have been extensively demonstrated for applications in nonvolatile memory, computer logic, and biological synapses. Precise control of the conducting paths associated with the resistance switching in memristive devices is critical for optimizing their performances including ON/OFF ratios. Here, gate tunability and multidirectional switching can be implemented in memristors for modulating the conducting paths using hexagonal α‐In2 Se3, a semiconducting van der Waals ferroelectric material. The planar memristor based on in‐plane (IP) polarization of α‐In2 Se3 exhibits a pronounced switchable photocurrent, as well as gate tunability of the channel conductance, ferroelectric polarization, and resistance‐switching ratio. The integration of vertical α‐In2 Se3 memristors based on out‐of‐plane (OOP) polarization is demonstrated with a device density of 7.1 × 10 9 in. −2 and a resistance‐switching ratio of well over 10 3 . A multidirectionally operated α‐In2 Se3 memristor is also proposed, enabling the control of the OOP (or IP) resistance state directly by an IP (or OOP) programming pulse, which has not been achieved in other reported memristors. The remarkable behavior and diverse functionalities of these ferroelectric α‐In2 Se3 memristors suggest opportunities for future logic circuits and complex neuromorphic computing. Abstract : Gate‐tunable and multidirection‐switchable memristive phenomena in a van der Waals ferroelectric α‐In2 Se3 are demonstrated. The planar memristor exhibits a pronounced switchable photocurrent, as well as gate tunability of the channel conductance, ferroelectric polarization, and resistance‐switching ratio. A multidirectionally operated α‐In2 Se3 memristor is also proposed, enabling the control of the out‐of‐plane (OOP) (or in‐plane (IP)) resistance state directly by an IP (or OOP) programming pulse.